Retinal and Corneal Toxicity and Pharmacokinetic Analysis of Intraocular Injection of Ganciclovir in Rabbit Eyes - Bin-jia Sun; Rong-mei Peng; Qing Lu; Jing Hong (Journal of Ophthalmology)
Purpose. To evaluate the safety and pharmacokinetic changes of ganciclovir (GCV) intraocular injection. Methods. GCV (2 mg/0.1 mL) was injected into rabbit eyes. Aqueous GCV concentration was detected by high-performance liquid chromatography. Potential toxicity was assessed by slit-lamp examination, optical coherence tomography, fundus examination, confocal microscopy, and histology. Results. Aqueous GCV concentrations were 24.83 ± 6.41 μg/mL, 0.65 ± 0.52 μg/mL, and undetected on the 1st, 3rd, and 7th day after intravitreal injection. GCV could not be detected on the first day after intracameral injection. No corneal abnormality was found after intravitreal injection, but retinal edema was observed on the first day which receded later. Corneal edema was obvious with endothelial cytoarchitecture damaged after intracameral injection; fluid retention also existed in retina. Conclusions. GCV intravitreal injection offers effective, sustained drug concentration in the anterior chamber, and its damage to retina receded over time. Intracameral injection results in rapid drug elimination and severe damage to endothelium and thus is not recommended.